Timing of Return to Pre-Pregnancy Training for Postpartum Elite Athletes: A Systematic Review and Meta-Analysis - Young-Min Park; Nyeonju Kang; Kwangseok Hong; Jinkyung Cho; Taekyung Han; Soo Hyun Park (운동과학)
PURPOSE Female athletes often face challenges in returning to exercise training programs after pregnancy and parturition. This study aimed to conduct a meta-analysis to investigate the optimal duration for elite female athletes to resume their pre-pregnancy training programs. METHODS Nine studies were included in this meta-analysis with a total of 1,466 women, comprising 567 nonathletes and 899 athletes. The effect sizes were calculated as differences in health-related indicators, athletic performance, and training volume during five periods: early, mid, and late pregnancy; within 6 months postpartum; and between 7 and 12 months postpartum, compared with pre-pregnancy levels. RESULTS Female athletes included in the study did not return to their pre-pregnancy physical condition even one year postpartum. Health indicators decreased substantially during pregnancy and remained lower than pre-pregnancy levels for up to one year postpartum. During pregnancy, there was a considerable reduction in training volume, which persisted throughout one year postpartum. However, athletic performance within the first year postpartum was not significantly different from pre-pregnancy levels; this finding is based on a single study, indicating a limitation due to the insufficient number of studies included in the analysis. CONCLUSIONS This study demonstrated that female athletes did not fully recover their physical condition or function within one year postpartum. Nevertheless, this finding does not imply that female athletes are unprepared or unable to resume exercise training within one year postpartum. Sufficient return to training can be achieved within this timeframe, but it is crucial to progressively and safely increase training volume and intensity in accordance with individual physiological recoveries.